Effect of Silkworm Pupae on the Growth and Egg Production Performance of Rhode Island Red (RIR) Pure Line - Khatun, R.; Azmal, S.A.; Sarker, M.S.K.; Rashid, M.A.; Hussain, M.A.; Miah, M.Y. (International Journal of Poultry Science, 2005)
A total of 63 day-old straight run Layer chicks up to 45 weeks of age on 3 isonitrogenous and isoenergetic diets D1 (6% PC+ 0% SWP), D2 (0% PC+ 6% SWP), and D3 (0% PC+ 8% SWP) were fed to observe the effect of dietary SWP on growth and egg production performance. This study revealed that profitability, growth and egg production performance of RIR pure line were significantly (P< 0.01) higher in D2 dietary treatment groups as compared to D1 and D3 treatment. No significant difference (P< 0.05) in livability was found which could be attributed to the dietary SWP levels. Feed cost/kg was gradually declined on increasing dietary levels of SWP. The efficiency by the birds receiving SWP were better as compared to the control. The result of this study demonstrated that cheaper SWP could be an excellent substitute of costly protein concentrate in formulating diets for layers leading to increase profitability.